If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7x+4-13x=-2+3x
We move all terms to the left:
7x+4-13x-(-2+3x)=0
We add all the numbers together, and all the variables
7x-13x-(3x-2)+4=0
We add all the numbers together, and all the variables
-6x-(3x-2)+4=0
We get rid of parentheses
-6x-3x+2+4=0
We add all the numbers together, and all the variables
-9x+6=0
We move all terms containing x to the left, all other terms to the right
-9x=-6
x=-6/-9
x=2/3
| -0.2x+12.4=-20-3.2x | | 30=-5-6(x-7) | | 5.37=3x+1.25 | | 2x-12-5x=7 | | 207=6x+5(5x-2) | | x-2/4=3x/8 | | 8+3m=-10 | | 3(2x-7)+10=16 | | 25=n-5 | | 2/3x=1/6 | | 10+m=20 | | 3n+3=4n-2 | | 5x-3=3(2x-1)-x | | (4*a)+7=-36 | | x/12=4;x= | | -6(-1+4n)-1=-91 | | 5+2n+2=12 | | 120x+0.30=50x+0.40 | | 3(x+2=4(x+1) | | (x+7)^2-36=0 | | 48/2=z | | 5x-2x+1=3x+15x-2/4 | | 1v+3=17 | | 56-11x+4x=77 | | -1=5x-16 | | x^2+20x+28=0 | | 4*x+7=36 | | y-2=22 | | 3n-5=7n-21 | | X^2/(.25-2x)^2=2 | | 2/5+1/10=1/2(n+4) | | 2n-5=9n+37 |